Fatwā on The Ruling of Hajj Without Taṣrīh; The Case of Indonesian Hajj Pilgrims in 2024 - Maram, Ahmad Nabilul; Said, Imam Ghazali; Tutik, Titik Triwulan (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
Compliance with government regulations and religious fatwas is essential to ensure the legality and safety of the hajj pilgrimage. However, performing hajj without a taṣrīh (official visa) has become a significant issue, particularly for Indonesian pilgrims with long waiting periods for official visas. This study examines the perspectives of religious scholars and fatwā institutions on the validity of hajj without taṣrīh factors that contribute to non-compliance and policy recommendations for Indonesian and Saudi authorities to address these violations. Using a qualitative case study approach, the research includes direct observation, in-depth interviews, and thematic analysis to explore the reasons and experiences of unauthorized pilgrims while depicting the perspectives of religious authorities and community leaders. Findings reveal that taṣrīh violations involve various actors, including individual pilgrims, public officials, and religious leaders like kiai, who use their influence to facilitate unauthorized hajj. Conflicting fatwas from authorities such as Nahdlatul Ulama, Muhammadiyah, and Hay'ah Kibār al-ʻUlamā’ add complexity to the issue. This study highlights the need for harmonized fatwā issuance and enhanced education on the implications of unauthorized hajj. Policy recommendations aim to improve compliance, align Sharia law with government regulations, and ensure a safe, orderly pilgrimage.